Difference in Nuchal Fold Thickness (NFT) in Male versus Female Fetuses [34B]. (May 2018) - Soni, Shelly; Rochelson, Burton; Blitz, Matthew J.; Vohra, Nidhi; Pessel, Caroline D.
Abstract : INTRODUCTION: To evaluate if second trimester nuchal fold thickness (NFT) differs in male vs female fetuses. We also assessed if male gender predisposes to an increased NFT. METHODS: Case control study of singleton pregnancies receiving second trimester fetal nuchal fold measurements identified from a search of ultrasound and cytogenetic databases. NFT was compared in male versus female fetuses. Data was stratified for fetuses with normal and increased NFT (defined as ≥6 mm from 14 weeks to 21.6 weeks of gestational age) as well as for those with abnormal genetic results. Genetic results were considered abnormal in cases of aberrant karyotype, as well as known pathogenic mutations on microarray or Noonan panel. RESULTS: Of the entire study group (N=6483 pregnancies), 51.3% fetuses (3328/6483) were males and 48.7% were females. Male fetuses had an increased mean NFT as compared to female fetuses in the entire cohort (4.2 mm in males versus 4.0 mm in females, p < 0.0001). NFT was higher in male fetuses in the normal NFT group as well as the group with increased NFT. Data was stratified based on gestational age in fetuses with normal NFT without known chromosomal aberrations. Male fetuses had a higher NFT across all gestational ages. Also, male fetuses had a higher incidence of increased NFT of ≥6mm when compared to female fetuses (OR 1.8 [1.3-2.5], P 0.0006). CONCLUSION: Male fetuses have a higher mean NFT as compared to female fetuses, and male gender predisposes to a higher likelihood of an increased NFT.